Efficacy of Preoperative Music Intervention on Pain and Anxiety in Patients Undergoing Cataract Surgery - Guerrier, Gilles; Bernabei, Federico; Lehmann, Mathieu; Pellegrini, Marco; Giannaccare, Giuseppe; Rothschild, Pierre-Raphaël (Frontiers in Pharmacology, 2021)
The aim of the present study was to investigate the impact of preoperative music exposure on intra- and post-operative pain during cataract surgery. This study was conducted alongside a prospective single-masked randomized controlled trial (ClinicalTrials.gov NCT02892825). Patients undergoing first eye cataract surgery were included and randomly assigned to either the intervention or control group. Patients in the intervention group had a 20-min music session through earphones before surgery, while patients in the control group wore earphones without music. Anxiety level evaluated using the visual analog scale and heart rate were collected before and after music intervention. Pain level was assessed using the Numerical Pain Rating Scale, during the surgical procedure, prior to discharge and 7 days postoperatively. A total of 243 patients were included: 119 in the intervention group and 124 in the control group. No significant differences in baseline characteristics, including age, sex and rate of treated hypertension were found between the 2 groups (all p-values > 0.05). In addition, no significantly differences were found in heart rate and anxiety level before music intervention between the 2 groups (all p-values > 0.05). Conversely, anxiety level was significantly lower in the music group after the intervention (respectively, 1.3 ± 1.1 vs 3.2 ± 2.2; p < 0.05). Patients in the music group reported a lower mean pain level during surgical procedure and before discharge compared with control group (respectively, 1.2 ± 0.5 vs 2.1 ± 1.1, p = 0.03 and 0.23 ± 0.4 vs 0.81 ± 0.7, p = 0.04). No difference was found in pain level 7 days postoperatively (0.1 ± 0.3 vs 0.2 ± 0.4, p = 0.1). A significant correlation was found between anxiety level and intraoperative pain level (R = 0.64, p = 0.02). In conclusion, music intervention was effective in reducing anxiety level and self-reported pain both during surgery and in the early postoperative period. Clinical Trial Registration:https://clinicaltrials.gov/ct2/home, identifier NCT02892825.